(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Latuconsina H, Kamal MM, Affandi R, Butet NA. 2021. Growth and reproductive biology of White-spotted rabbitfish (Siganus canaliculatus) on different seagrass habitats in Inner Ambon Bay, Indonesia. Biodiversitas 23: 273-285. Seagrass meadows are one of the important habitats for Siganus canaliculatus. This study aimed to compare the growth and reproductive biology of S. canaliculatus in different seagrass habitats on the Inner Ambon Bay. A fish sampling was observed once a month for a year (15 August 2018-20 July 2019) using a beach seine. The data analysis included growth patterns, condition factors, sex ratio, gonadal maturity, gonado somatic index, size at first maturity, and fecundity. The study results obtained body Length and weight varied between seagrass habitats, with an isometric growth pattern. The equation W: 0.0105 L3,1007 male and W: 0.0165L2,9444 female in mixed vegetation, while for monospecific vegetation, male W: 0.0109L3,0891 and female W: 0.0143L3,0067. The value of condition factors, sex ratio, size at first maturity, and fecundity differed between seagrass habitats. The range of fecundity is 198,000-783,750 eggs, and there is a positive relationship between body length and weight with fecundity. A technical approach to fisheries management is needed, namely: (i) the size at first maturity is used as a reference for the size of fish that can be caught, and (ii) determination of mixed vegetation seagrass as a conservation area; and monospecific vegetation as fishing grounds.